PENGEMBANGAN MEDIA PEMBELAJARAN MULTIKULTURAL BERBASIS AUDIOVISUAL UNTUK MENANAMKAN NILAI KARAKTER TOLERANSI PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V SEKOLAH DASAR - Setiawan, Andi; Rossi Iskandar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop and test the feasibility and effectiveness of audiovisual-based multicultural learning media to instill the character value of tolerance in Pancasila Education for fifth-grade elementary school students. The study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of the study were fifth-grade students at SDN Kebon Baru 07 in South Jakarta, which implements the Merdeka Curriculum. The analysis stage showed that students tend to prefer visual learning, but the media used by teachers is limited to textbooks, which leads to suboptimal student interest in learning. Based on validation by media experts (score 4.42, very valid category), language experts (score 5.00, very valid category), and material experts (score 5.00, very valid category), the developed media was declared feasible for testing. The results of the effectiveness test using a pre-test and post-test with N-gain calculations on a small scale (N-gain = 0.4), medium scale (N-gain = 0.48), and large scale (N-gain = 0.39) showed a